Exploratory Study: Forms of Animism and Dynamism in the Islamic Religious System and Culture in the Indigenous Community of Kampung Kuta, Ciamis District - Saepulmilah, Ceceng; Azhari, Septian Cahya; Isnawati, Isnawati (Center for Research and Publication (PUSLITPEN), UIN Syarif Hidayatullah Jakarta, 2024)
This exploratory study delves into the intricate interplay between animism, dynamism, and the Islamic religious system within the indigenous community of Kampung Kuta in Ciamis District. Despite the predominant influence of Islam in the region, the inhabitants of Kampung Kuta have maintained a unique blend of traditional animistic beliefs and dynamic cultural practices, shaping a distinctive religious landscape. The research employs a qualitative approach, utilizing ethnographic methods such as participant observation and in-depth interviews to unravel the nuanced expressions of animism and dynamism within the community's religious framework. The results of this study indicate that Nyuguh is an inseparable part of the culture of the Kuta village community and collaborates with the values of Islamic religious ideology. The conclusions of this study can inform future research on the complex relationship between Indigenous spirituality and religious ideology, encouraging a more comprehensive understanding of religious dynamics in diverse cultural settings.